If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(6 + 6X) = 60 (6 * 5 + 6X * 5) = 60 (30 + 30X) = 60 Solving 30 + 30X = 60 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 30X = 60 + -30 Combine like terms: 30 + -30 = 0 0 + 30X = 60 + -30 30X = 60 + -30 Combine like terms: 60 + -30 = 30 30X = 30 Divide each side by '30'. X = 1 Simplifying X = 1
| 15-6y=1-4y | | 0.5s=4s*21 | | 8n+9(n+3)= | | 8n+9= | | 6x-4=6(x-1) | | 0.67(6x-9)=x+5 | | -8x^2(-17x^2+46)= | | 0.25x+y=4 | | 15(x-8)=x+2-(2x+5) | | w^2-3w+2= | | 5(x-8)=x+2-(2x+5) | | -6(v+2)+3v+6=6v+7 | | (4x+6y+9)(4x+6y-9)= | | 4r=22 | | 6x-10=6(x-2) | | -2(8p+2)-3(2-7p)-2(4+2p)=0 | | 4v-10-4v=5 | | 6(4-5X)=234 | | (2x+13)(2x+13)=8 | | (9x+1)(9x-1)= | | 5(-6X-7)=145 | | 16t^2+84t= | | 5(1+4y)=2(3+10y) | | 2(2-x)-(4-x)=-5 | | 2.5a-6=1.12a-1.86 | | x^2-15+x^2-36= | | 9(x+12)-4x=143 | | -3(w+5)+7=-23 | | 3x+1-5(x+1)=6x+3 | | -7(-6X-2)=-448 | | X(2x+1)=105 | | -2y=14 |